ANALISIS PENGENDALIAN KUALITAS PRODUK PADA USAHA HOME INDUSTRY FURNITURE BAPAK KARSIDIN DI KELURAHAN LOKBAHU KECAMATAN SUNGAI KUNJANG KOTA SAMARINDA - DODY AL'AZHAR (Jurnal Administrasi Bisnis Fisipol Unmul, 2020)
Product quality control is very important for company or business that is willing to improve the performance. Home Industry Business or a home-based business established by Mr. Karsidin is furniture business and the products include cabinet, table, bench, TV rack and other furniture items which can be tailored to customer desires. In the production process, Mr. Karsidin's business still has product defects that can be observed at the beginning of this study that is presented in table 1.1. The study aims to determine the product quality level is still in control limits measurement of Mr. Karsidin’s Home Industry Business, analyze types of defects and control production quality using statistical quality control (SQC). The method in the study was statistical quality control (SQC) to monitor standards, make measurements and take corrective actions while the product or service is being produced. The quality control tools were Observation Sheet, Histogram, Cause and Effect Diagram and Control Diagram (p Chart). The result indicates that the product quality by Mr. Karsidin's business during the observation period from April to May 2019 is at the control limit. Further, based on p control analysis there is no point that exceeds Upper Limit or Lower Limit. The production process should be given more attention, especially at several main factors such as workers or human factors, in which there are a lot of negligence in the production process. Mr. Karsidin should make improvement to the defects directly that at the cause level, including raw material, machinery, method and human factors based on the Standard Operating Procedures (SOP).